Characterisation of a monoclonal antibody raised against a thermostabilised β1-adrenoceptor - Soave, Mark (2017)
The β1-adrenoceptor (β1-AR) is an important regulator of cardiac function. Chronic stimulation and subsequent downregulation of cardiac β1-ARs have been implicated in heart failure. Recently, it has been demonstrated that antibodies which target the second extracellular loop (ECL2) of the human β1-AR play a role in the pathogenesis of some forms of cardiomyopathy. Heptares Therapeutics Ltd. developed a murine monoclonal antibody (mAb3) raised against the thermostabilised turkey β1-adrenoceptor which had ECL2 as the epitope. MAb3 was previously characterised in CHO cells transiently expressing the turkey β1-AR. This thesis characterises the pharmacology of mAb3 at the human and turkey β1-AR in stable CHO cell lines.